Wanprestasi Perjanjian Repurchase Agreement di Pasar Modal yang Berdampak Kerugian Investor Dihubungkan dengan Peraturan Otoritas Jasa Keuangan Nomor 9/Pojk.04/2015 Tentang Pedoman Transaksi Repurchase Agreement bagi Lembaga Jasa Keuangan - Muhammad Juniardi Putra; Ratna Januarita (Bandung Conference Series: Law Studies, 2024)
Abstarct. Guidelines regarding transactions repurchase agreement (REPO) has been regulated by the Financial Services Authority (OJK), but in practice there are still cases where one of the parties experiences losses due to non-compliance with the agreement in practice due to an action that is not in accordance with the agreement. The approach method used in this research is the Normative Juridical approach, namely a legal approach carried out by examining library materials or secondary data. This research is descriptive analytical in nature, which provides a description of an object being studied through the data collected, apart from that the analysis is also carried out based on relevant and latest laws and regulations in order to get answers to the problems being studied. Implementation of a repurchase agreement (REPO) transaction agreement, in this case the seller and buyer must enter into a written agreement that complies with the provisions of Financial Services Authority Regulation Number 9/POJK.04/2015. In relation to liability for default, the aggrieved party can take legal action in Article 1267 of the Civil Code, namely by requesting implementation of the contents of the agreement if it can still be implemented, requesting compensation, requesting cancellation of the agreement as well as compensation. Implementation of the repurchase agreement (REPO) transaction must be based on the agreement. written and implementing GMRA. Meanwhile, Financial Services Authority Regulation Number 9/POJK.04/2015 states that if an event of failure occurs, all parties must complete their obligations in accordance with the procedure for resolving the event of failure as well as the related rights and obligations that have been regulated in the repurchase agreement (REPO) transaction agreement.